Management Framework for a High-Value of Agricultural Product to Increase Income for Farmers in Rural Area - Khuntonthong*, Puttawan; Chakpitak, Nopasit; Neubert, Gilles (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
This research aims to study how to manage a high-value agricultural product to be launched as alternative to generate income for rural farmers. Bresse chicken, a specialty variety of chicken originating in France, introduced to farmers in Thailand by the Royal Project Foundation is selected to be a case study as it has potential to help farmers increase income. In order to promote this type of chicken under the existing competitive environment, the understanding in the structure of industry and the strategies to compete in the market are needed. The attractiveness and competitiveness of Bresse chicken in the market are analyzed by employing Five Forces Model. The competitive strategies to deliver this product to market can be formulated and used as guidance to manage Bresse chicken effectively. Keywords: High-value Crop, Farmer, Remote Area, Income, Five Forces Model, Competitive Strategy Email: p.khuntonthong@gmail.com